Carbon nanosheets by the graphenization of ungraphitizable isotropic pitch molecules - Lee, Jae-Seon; Kim, Young-Kwan; Hwang, Jun Yeon; Joh, Han-Ik; Park, Chong Rae; Lee, Sungho (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
We report a tremendous structural evolution of carbon nanosheets (CNSs) through the graphenization of isotropic pitches prepared by reforming commercially available naphtha cracking bottom oil. CNSs with thicknesses of 2-13 nm were prepared by spincoating on quartz substrates directly without a catalytic material, followed by two successive thermal treatments consisting of stabilization at 270 degrees C in air and carbonization at up to 1200 degrees C in H2/Ar. The development of wellordered graphene layers around pebblelike structures with increasing carbonization temperature was observed in only the 13nm thick CNSs by transmission electron microscopy, whereas thin CNSs did not reveal welldeveloped fringe growth. In addition, Raman, UVevis, and Xray photoelectron spectroscopies along with mass spectrometry unanimously showed clear evidence indicating that unusually welldeveloped crystalline structure was formed in the thick CNSs. It should be noted that isotropic pitches, which are intrinsically nongraphitizable carbon sources, evolved into highly ordered structures at a relatively low carbonization temperature (1200 degrees C). We believe that the graphenization of spincoated films of pitch molecules resulted from the condensation of small pitch molecules and their selfassembled structure during carbonization under the anisotropic pressure induced by significant shrinkage in the vertical axis. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: DESORPTION/IONIZATION MASS-SPECTROMETRY; MESOPHASE-PITCH; STRUCTURAL-CHARACTERIZATION; OXIDATIVE STABILIZATION; RAMAN-SPECTROSCOPY; PETROLEUM PITCH; HARD CARBONS; FIBERS; GRAPHITIZATION; SURFACE